Efficacy of, and toxicity associated with, the use of levamisole in seawater to treat amoebic gill disease - Munday, BL; Zilberg, D (2003)
Atlantic salmon smolts with severe amoebic gill disease (AGD) and bathed in 50 ppm levamisole in seawater showed resolution of lesions and survival comparable with that of cohorts treated by a freshwater bath. However, high mortality occurred in smolts with extreme AGD when they were bathed in 50, 25 and 12.5 ppm levamisole in seawater. The possible mechanisms involved in relation to these observations are discussed.